2015
DOI: 10.1136/injuryprev-2015-041786
|View full text |Cite
|
Sign up to set email alerts
|

Injury incidence among middle school students aged 13–15 years in 47 low-income and middle-income countries

Abstract: A total of 95 811 students aged 13-15 years participated in nationally representative Global School-based Student Health Surveys (GSHS) in 47 low-income and middle-income countries conducted between 2003 and 2012. On average, about 40% of the participants in each country reported at least one injury in the past year that was serious enough to cause the student to miss at least one full day of usual activities (such as school, sports and a job) or to require treatment by a healthcare professional. In 40 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
4
14
0
Order By: Relevance
“…Moreover, males were significantly more likely than females to sustain at least one sports injury in all but one of the surveyed countries. This is consistent with another study that found that boys had a higher all-cause injury rate in 40 of 47 LMICs [6]. Third, injury rates vary widely between countries.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, males were significantly more likely than females to sustain at least one sports injury in all but one of the surveyed countries. This is consistent with another study that found that boys had a higher all-cause injury rate in 40 of 47 LMICs [6]. Third, injury rates vary widely between countries.…”
Section: Discussionsupporting
confidence: 91%
“…However, the extent to which sports injuries contribute to the global burden of injury is poorly documented. Large schoolbased cohort studies, injury databases, and surveillance systems have provided some information on the incidence of sports injuries in high-income countries (HICs) [7][8][9][10][11][12], but comparable studies from low-and middle-income countries (LMICs) are lacking [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…This result was also previously found [6,7,17,18]. Substance use (ever using drugs in Cambodia and current alcohol use in Vietnam) was, as also identified in previous studies [6,17], associated with injury in this adolescent population.…”
Section: Discussionsupporting
confidence: 89%
“…The annual nonfatal injury prevalence found was higher in Vietnam (34.3% among boys and 25.1% among girls) than in Cambodia (22.6% among boys and 17.5% among girls), which seems lower than the median from global studies of 25 developing countries (44% among boys and 30% among girls) [8] and 47 developing countries (median 40%) [18], but similar to findings from Myanmar (27%) [6]. However, the current annual prevalence of nonfatal injury in Cambodia and Vietnam seems to be higher than in previous large, population-based surveys among adolescents in Cambodia (5.3% among males and 2.7% among females) [9] and Vietnam (5%) [10].…”
Section: Discussionmentioning
confidence: 91%
“…In 2016, foreach unintentional injury loss to those ages 0-19 there were nearly 33 hospitalizations and 1053 emergency unit visits (CDC, 2018). The mean value of unintentional injury in low-and middle-income countries (LMICs) was 40% (Street & Jacobsen.,2016). Reports in Palestine (47.6%) (Jildeh et al, 2013), Nigeria (73.6%) (Azubuike and Onyemaka, 2012), and Malaysia (34.9%) (Peltzer and Pengpid, 2015) are some of the examples from LMICs.…”
Section: Introductionmentioning
confidence: 99%